2006
DOI: 10.1111/j.1365-2672.2005.02783.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of the bacteria adherent to human colorectal mucosa

Abstract: Aims: To study large intestinal mucosal bacterial communities by Denaturing Gradient Gel Electrophoresis (DGGE) profiling and sequencing of 16S rRNA gene polymerase chain reaction (PCR) products amplified from DNA extracted from colorectal biopsies taken from healthy individuals. The specific aims were to determine how similar the mucosa-associated bacterial communities are within and between individuals and also to characterize the phylogenetic origin of isolated DGGE bands. Methods and Results: Human colorec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 32 publications
(68 reference statements)
4
51
1
Order By: Relevance
“…Many of the other bacteria enriched on the mucosa, such as Campylobacter spp., Weissella spp, and Sutterella spp., are known mucosal colonizers or pathogens and are likely mucosal specialists (On, 1996). These genera may be broadly specific to mucosal surfaces across mammals, having been identified on the mucosal surfaces of multiple host species (On, 1996;Heilig et al, 2002;Green et al, 2006). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the other bacteria enriched on the mucosa, such as Campylobacter spp., Weissella spp, and Sutterella spp., are known mucosal colonizers or pathogens and are likely mucosal specialists (On, 1996). These genera may be broadly specific to mucosal surfaces across mammals, having been identified on the mucosal surfaces of multiple host species (On, 1996;Heilig et al, 2002;Green et al, 2006). …”
Section: Discussionmentioning
confidence: 99%
“…Resident bacteria benefit from nutrient-rich digesta while assisting the host via nutrient digestion, vitamin synthesis, pathogen displacement and immune system maturation (Green et al, 2006;Bird et al, 2010). Factors such as nutrient availability, pH, redox potential and peristalsis strongly influence the composition of bacterial communities in the intestinal tract (Hao and Lee, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Highly conserved regions of the 16S rRNA gene enable amplification of this gene from most bacteria with "universal" PCR primers, while variable regions within this gene permit discrimination between bacterial types (16). This approach has been applied successfully to the analysis of environmental (2,20,35,37,42) and human (18,26,28,29,38) bacterial communities and has revealed a much broader bacterial diversity than has traditional culture-based techniques (38). However, to our knowledge, no previous study has examined the extent of bacterial diversity within the lungs of intubated patients by culture-independent methods.…”
Section: Management Of Airway Infections Caused Bymentioning
confidence: 99%
“…Despite these observations, and the technological advances that have been applied to the analysis of gut microbial communities, evidence of a biogeographical pattern within the microbiome of the human large intestine has been elusive to obtain, principally because of the high degree of intersubject variability and constraints in sample number and size. A number of studies have shown a lack of variation in the mucosa-associated microbial communities along the human colon (Zoetendal et al, 2002;Lepage et al, 2005;Bibiloni et al, 2006;Green et al, 2006;Willing et al, 2009) and between diseased and healthy mucosal tissue Vasquez et al, 2007). These studies have usually relied on alphaand beta-diversity measures for the comparative analysis of microbial communities.…”
Section: Introductionmentioning
confidence: 99%